Vida Saludable: Presión sanguínea alta - Leigh Ann Martin; Linda B. Bobroff (EDIS)
Revised! FCS8599Span, a 1-page illustrated fact sheet by Leigh Ann Martin and Linda B. Bobroff, is the Spanish language version of FCS8599/FY684 Healthy Living: High Blood Pressure. In brief it explains what high blood pressure is, what hypertension can cause, risks, how it affects the arteries, and the importance of regular blood pressure check-ups. Published by the UF Department of Family Youth and Community Sciences, November 2009.